2021
DOI: 10.5194/gmd-14-7345-2021
|View full text |Cite
|
Sign up to set email alerts
|

STEMMUS-UEB v1.0.0: integrated modeling of snowpack and soil water and energy transfer with three complexity levels of soil physical processes

Abstract: Abstract. A snowpack has a profound effect on the hydrology and surface energy conditions of an area through its effects on surface albedo and roughness and its insulating properties. The modeling of a snowpack, soil water dynamics, and the coupling of the snowpack and underlying soil layer has been widely reported. However, the coupled liquid–vapor–air flow mechanisms considering the snowpack effect have not been investigated in detail. In this study, we incorporated the snowpack effect (Utah energy balance s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Current SW-GW modelling work seldom considers the thermal effect and lacks real-case applications and verifications (see Appendix Table A2). The developed SW-GW coupling model in this work will facilitate 445 further the manipulation of sub-models with different complexity of vadose zone physics (thermal flow, soil water and heat coupling transfer, freeze-thaw, airflow processes; Yu et al, 2020b), surface hydrology (snowfall, Yu et al, 2021, runoff, Mastrotheodoros et al, 2020, connection with other relevant processes (soil and plant biogeochemical process, Yu et al, 2020a), towards an integrated groundwater-soil-plantatmosphere earth system modelling framework. 450…”
Section: The Limitations and Outlookmentioning
confidence: 99%
“…Current SW-GW modelling work seldom considers the thermal effect and lacks real-case applications and verifications (see Appendix Table A2). The developed SW-GW coupling model in this work will facilitate 445 further the manipulation of sub-models with different complexity of vadose zone physics (thermal flow, soil water and heat coupling transfer, freeze-thaw, airflow processes; Yu et al, 2020b), surface hydrology (snowfall, Yu et al, 2021, runoff, Mastrotheodoros et al, 2020, connection with other relevant processes (soil and plant biogeochemical process, Yu et al, 2020a), towards an integrated groundwater-soil-plantatmosphere earth system modelling framework. 450…”
Section: The Limitations and Outlookmentioning
confidence: 99%
“…(2011a, 2011b) developed the simultaneous transfer of energy, mass, and momentum in unsaturated soil (STEMMUS) model, which considers dry air as a single phase, and includes soil air pressure as a state variable in soil water and heat transport. This model has recently been successfully used to simulate hydrological processes in frozen soils (Yu, Fatichi, et al., 2020; Yu, Zeng, & Su, 2020; Yu et al., 2018, 2021). It has also been demonstrated that the incorporation of airflow improves the simulation accuracy of soil moisture when significant precipitation occurs (J. X. Wang et al., 2021; Yu, Fatichi, et al., 2020; Yu, Zeng, & Su, 2020, Yu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The frozen soil region is rich in natural resources, while many projects in China, such as energy, transportation, communication, water, and oil pipelines, are established in the frozen soil region (Zhang et al, 2015;Che et al, 2019;Ma et al, 2019;Streletskiy et al, 2019). The distribution and form of pore accesses in frozen soil vary, the momentum, energy, and mass transfer processes interact, and couple with each other, and the transfer phenomena and mechanisms are complex and variable (Sweidan et al, 2022;Yu et al, 2021;Fu et al, 2022). Some of the essential characteristics are difficult to obtain precisely (Alzoubi et al, 2019;Chang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%